PENGARUH NET PROFIT MARGIN, RETURN ON EQUITY, RETURN ON ASSETS, CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021 – 2023 - Akash Raj Singh; Deni Sastra Solin; Jenny Zain; Oky Syahputra (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this study is to determine the effect of Net Profit Margin, Return On Equity, Return On Assets, Current Ratio on Stock Prices in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2021 - 2023. The method used in this study is a quantitative method. The results of the study are that Net Profit Margin has a positive and significant effect on stock prices. Return On Equity partially does not have a significant effect on Stock Prices. Return On Assets tends to have a positive effect on stock prices, but its effect is not statistically significant at the 95% confidence level. Current Ratio does not have a significant effect partially on stock prices. However, simultaneously, Net Profit Margin, Return On Equity, Return On Assets, and Current Ratio have a significant effect on Stock Prices.